Comparison of DNA isolation protocols from soybean - Guzmán Rodríguez, Luis Felipe; Cortés Cruz, Moisés A.; Pichardo González, Juan Manuel; Arteaga Garibay, Ramón Ignacio (Revista Mexicana de Ciencias Agrícolas, 2018)
The low efficiency of some nucleic acid extraction protocols and the high cost of commercial products, derives in the comparison between methods. In the present work three DNA extraction methods were compared from soybean, to obtain nucleic acids of adequate concentration and quality for PCR amplification. The protocols studied included the methods with 1% and 3% CTAB solutions, with 1% sarcosine and with phenol/chloroform. The experiments were carried out in the DNA and Genomics laboratory of the National Genetic Resources Center-INIFAP. The yield, purity, integrity and functionality of the obtained nucleic acids were evaluated. In all methods, adequate DNA yield was achieved, however, the required purity of the material was only obtained with the phenol/chloroform solution. With the methods of CTAB at 1% and 3% and sarcosine, PCR inhibiting substances were observed, while, with phenol/chloroform, the values of the A260/280 ratio were in a range of 1.96 to 2.00 and the A260/230 ratio in a range of 1.75 to 2.44, with significant differences (p< 0.0001) with the rest of the methods, in addition, the DNA was of high molecular weight and the rbcL gene was amplified by PCR in all the samples. The use of the phenol/chloroform protocol allowed to obtain from soybean, nucleic acids of adequate concentration and quality for PCR amplification.
Keywords: DNA extraction; DNA quality; nucleic acids